Artifact reduction strategies for prosthetic heart valve CT imaging - Habets, Jesse (Springer Netherlands, 2012)
Multislice CT evaluation of prosthetic heart valves (PHV) is limited by PHV-related artifacts. We assessed the influence of different kV settings, a metal artifact reduction filter (MARF) and an iterative reconstruction algorithm (IR) on PHV-induced artifacts in an in vitro model. A Medtronic-Hall tilting disc and St Jude bileafet PHV were imaged using a 64-slice scanner with 100 kV/165 mAs, 120 kV/100 mAs, 140 kV/67 mAs at an equal CTDIvol. Images were reconstructed with (1) filtered back projection (FBP), (2) IR, (3) MARF and (4) MARF and IR. Hypo- and hyperdense artifacts volumes (mean mm3 ± SD) were quantified with 2 thresholds (≤−50 and ≥175 Hounsfield Units). Image noise was measured and the presence of secondary artifacts was scored by 2 observers independently. Mean hypodense artifacts for the Medtronic-Hall/St Jude valve (FBP) were 966 ± 23/1,738 ± 21 at 100 kV, 610 ± 13/991 ± 12 at 120 kV, and 420 ± 9/634 ± 9 at 140 kV. Compared to FBP, hypodense artifact reductions for IR were 9/8 %, 10/7 % and 12/6 % respectively, for MARF 92 %/84 %, 89/81 % and 86/77 % respectively; for MARF + IR 94/85 %, 92/82 %, and 90/79 % respectively. Mean hyperdense artifacts for the Medtronic-Hall/St Jude valve were 5,530 ± 48/6,940 ± 70 at 100 kV, 5,120 ± 42/6,250 ± 53 at 120 kV, and 5,011 ± 52/6,000 ± 0 at 140 kV. Reductions for IR were 2/2 %, 2/3 % and 3/4 % respectively, for MARF were 9/30 %, 0/25 %, 5/22 % respectively, MARF + IR 12/32 %, 4/27 % and 7/25 % respectively. Secondary artifacts were found in all MARF images. Image noise was reduced in the IR images. In vitro PHV-related artifacts can be reduced by increasing kV despite maintaining identical CTDIvol. Although MARF is more effective than IR, it induces secondary artifacts.